Surgical treatment of secondary cicatricial alopecia of scalp and eyebrow - Ahmed Sabry Hassan (Indian Journal of Plastic Surgery, 2009)
Secondary cicatricial alopecia occurs as a result of destruction of hair follicles by scar tissue formed in the scalp and eyebrows. It is a permanent condition and regrowth of hairs in the area is not expected. The purpose of the study was to select the appropriate method for treating cicatricial alopecia. 24 patients were admitted to our hospital during the period from June 2006 to July 2007. They were suffering from acquired cicatricial alopecia affecting the scalp and the eyebrow. Their ages ranged from 6-48 years with mean age 26-25 years. They were treated surgically by total excision of the lesions with direct closure of the defect in ten cases, excision of alopecia with advancement flaps with the aid of scalp expanders in seven cases, scalp reduction through serial excision of alopecia in three cases and excision of alopecia and reconstruction of the defect by strip composite hair-bearing scalp grafts in four cases. Our results suggest there are three key factors that decide the surgical methods for treating alopecia: size, location and shape. We also discuss and evaluate the various techniques of reconstruction. Good results were obtained in 18 patients.